A systems approach to life cycle risk prediction for complex engineering projects. Issue 1 (1st January 2018) - Cook, Matthew; Mo, John P.T.
Abstract: In order to successfully deliver challenging and complex engineering projects, it is essential that an organisation has an in-depth understanding of the technical and commercial risks. Without this knowledge, decisions can fail to address, manage or mitigate potential and residual risks causing cost blowouts, schedule delays and technical failures. This paper presents a new method that both quantifies and models the relative risk profile of a project throughout the project lifecycle. It allows the continued management and visualisation of risks and enables a process of dynamic analysis to both reduce and/or mitigate residual risks progressively to acceptable levels. This research explores the use of an enterprise model based on three elements: product, process and people. These elements interact but are constrained in a business/engineering environment. The elements can be used to develop a ubiquitous set of generic project risks prevalent across complex engineering projects. The method is illustrated by three case studies taken from the defence environment, but, the general theory and method can be applied to non-defence organisations and industries.